Analysis of SVC and TCSC controllers in voltage collapse - Canizares, Claudio A.; Faur, Zeno T. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This paper presents detailed steady-state models with controls of two flexible AC transmission system (FACTS) controllers, namely, static VAr compensators (SVCs) and thyristor controlled series capacitors (TCSCs), to study their effect on voltage collapse phenomena in power systems. Based on results at the point of collapse, design strategies are proposed for these two controllers, so that their location, dimensions and controls can be optimally defined to increase system loadability. A European system is used to illustrate the application of all proposed models and techniques.
Keywords: FACTS; SVC; TCSC; Voltage collapse; Loadability margin; Bifurcations.